2022
DOI: 10.1021/acsabm.1c01277
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion Resistance and Biocompatibility of Calcium Phosphate Coatings with a Micro–Nanofibrous Porous Structure on Biodegradable Magnesium Alloys

Abstract: Magnesium (Mg) and its alloys have exhibited great potential for orthopedic applications; however, their poor corrosion resistance and potential cytotoxicity have hindered their further clinical applications. In this study, we prepared a calcium phosphate (Ca−P) coating with a micro−nanofibrous porous structure on the Mg alloy surface by a chemical conversion method. The morphology, composition, and corrosion performance of the coatings were investigated by scanning electron microscope (SEM), energy-dispersive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…The Y 01 of the Mg alloy, the DCPD-coated sample, the DCPD/PCL-coated sample, and the DCPD/PCL/Cu-ADCP-coated sample decreased sequentially, which suggested that the corrosion area decreased accordingly, as shown in Table . Additionally, the R 1 of the DCPD-coated sample was twice as large as that of the Mg alloy, demonstrating more effective protection.…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…The Y 01 of the Mg alloy, the DCPD-coated sample, the DCPD/PCL-coated sample, and the DCPD/PCL/Cu-ADCP-coated sample decreased sequentially, which suggested that the corrosion area decreased accordingly, as shown in Table . Additionally, the R 1 of the DCPD-coated sample was twice as large as that of the Mg alloy, demonstrating more effective protection.…”
Section: Resultsmentioning
confidence: 89%
“…The Y 01 of the Mg alloy, the DCPD-coated sample, the DCPD/PCL-coated sample, and the DCPD/PCL/Cu-ADCPcoated sample decreased sequentially, which suggested that the corrosion area decreased accordingly, as shown in Table 1. 34 Additionally, the R 1 of the DCPD-coated sample was twice as large as that of the Mg alloy, demonstrating more effective protection. After filling the pores of the DCPD with PCL, R 1 increased by an order of magnitude, confirming that the corrosion resistance of the chemical conversion coating could be improved by healing the pores.…”
Section: Electrochemical Corrosionmentioning
confidence: 94%
“…The deposition temperature affected the activity of ions in the solution and thus became a decisive factor affecting the nucleation of calcium and phosphorus on the cathode surface . The increase in temperature accelerated the molecular thermal motion, resulting in faster ion migration, thereby increasing the reaction rate, which led to the scale size gradually becoming smaller and finer . When the hydrolysis reaction was promoted at high temperatures, the hydrogen evolution along with it changed the growth direction of the calcium–phosphorus crystal nucleus from horizontal to inclined to vertical fibrous, which also make the coating structure more loose.…”
Section: Resultsmentioning
confidence: 99%
“…30 The increase in temperature accelerated the molecular thermal motion, resulting in faster ion migration, thereby increasing the reaction rate, which led to the scale size gradually becoming smaller and finer. 31 When the hydrolysis reaction was promoted at high temperatures, 32 the hydrogen evolution along with it changed the growth direction of the calcium− phosphorus crystal nucleus from horizontal to inclined to vertical fibrous, which also make the coating structure more loose. At higher deposition temperatures, the grain nucleation process had anisotropy, and the growth rate of the grain in the axial direction was much higher than that in the radial direction, so the preferred orientation of the C-axis was presented, and the fibrous structures with a higher aspect ratio was obtained.…”
Section: Resultsmentioning
confidence: 99%
“…Su et al [ 34 ] studied the preparation process of calcium phosphate conversion coating (CPCC) and determined that the pH value and temperature of the reaction significantly affect the coating structure and porosity, which can affect the corrosion performance of CPCC coatings. It is worth noting that Guo et al [ 35 ] looked at more than just how calcium phosphorus coating affected magnesium alloys’ ability to withstand corrosion, and studied the biocompatibility of Ca-P coating through in vitro experiments. The experimental results indicate that Ca-P coating can significantly increase the magnesium alloys’ resistance to corrosion and biocompatibility, providing a theoretical basis for the application of Ca-P as a coating material in medical magnesium alloys.…”
Section: Introductionmentioning
confidence: 99%